Gendered Career Paths for Saskatchewan Educators: A Century of Change - Corman, June (Atlantis, 2010)
Drawing on interviews, archival research and statistical data, this paper compares the status of women and men in the teaching profession in Saskatchewan through an examination of changes over time in the sex composition of teachers, marital status, geographic distribution, salary scales and administrative duties.